Designing an Accesible User Interface Web Platform - Kirichuk, Ekaterina; Jílková, Petra; Dědic, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The primary goal of this bachelor's thesis is to develop an accessible low-fidelity prototype of the Make web application by integrating principles of accessible design and usercentered design, thereby strengthening digital inclusion. This thesis investigates the UX enhancement of accessibility through the development of prototypes designed to support screen readers and keyboard navigation. The theoretical framework examines legislative, ethical, and business considerations of web accessibility, alongside a review of assistive technologies and methodologies for accessibility analysis. The practical segment of the research began with an accessibility audit of the existing Make application to identify current features and deficiencies. This audit informed the development of three innovative low-fidelity prototypes: an improved user interface (UI) that facilitates easier navigation within the application's scenario builder, a customizable accessibility settings window, and a comprehensive list of keyboard shortcuts. These features were designed based on principles discussed in the theoretical part and refined through user feedback. Additionally, the study involved user experience testing with five participants, who provided valuable insights and suggestions for further enhancements. The prototypes not only serve as a blueprint for future high-fidelity development but also engage potential users in the iterative design process. Overall, this thesis delivers a critical accessibility analysis of the Make application and proposes practical solutions to enhance its usability for individuals relying on assistive technologies. The outcomes underscore the importance of inclusive design and usercentered development in creating accessible digital environments.
Vedoucí práce: Petra Jílková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses